Structural and Content Model for the Formation of Foreign-Language Communicative Competence in Students of Natural Science Specialties within Professionally Oriented Education - Baigulina, Elmedira; Uzakbayeva, Sahipzhamal; Amirova, Lyazzat; Bekdualieva, Ainur; Aitbayeva, Dilda (Jurnal Pendidikan IPA Indonesia, 2025)
The aim of this study is to develop and substantiate a structural and content model for the formation of foreign language communicative competence (FLCC) in students of natural science specialties within the context of professionally oriented education. The research identifies the key components of FLCC, including linguistic, sociocultural, pragmatic, and strategic elements, alongside essential subcompetencies crucial for effective communication in both scientific and professional contexts. The study utilizes a blend of professional-competence, professional-personality-oriented, professional-interactive, and subject-professional approaches to ensure alignment with modern professional standards and to address the individual learning needs of students. It also outlines the necessary linguodidactic conditions for the successful implementation of the model, emphasizing the integration of foreign language training with specialized scientific disciplines, the promotion of active communicative practices, the enhancement of students’ academic autonomy, and the modular structuring of content. The results demonstrate the effectiveness of this approach in systematically developing students’ capacity for professional and scientific communication in a foreign language. This study contributes to the field of language education by offering a comprehensive framework for developing FLCC in line with the demands of the international academic and professional environments.